Learning strategies and vocabulary mastery benefits through Spotify application: An explanatory study - Asri Siti Fatimah; Kantia Aprida Salma; Neni Marlina (UIN Raden Mas Said Surakarta, 2026)
Despite the widespread use of digital music platforms for vocabulary learning, limited research has examined how English songs on Spotify facilitate students’ vocabulary learning strategies and contribute to their lexical development. This study aims to discover university students' language learning strategies when learning vocabulary through English songs on Spotify and its benefit on their vocabulary mastery. An explanatory case study was used as a research method. The participants consisted of three undergraduate students majoring in English Education at a university in Tasikmalaya, West Java, Indonesia. The data were collected using semi-structured interviews and analyzed by thematic analysis, guided by language learning strategies framework. The results showed that students employed a combination of cognitive, affective, and metacognitive strategies including repeated listening to reinforce lexical retention, strategic use of platform features and online tools to clarify meaning and pronunciation and deliberate organization of activities. Participants mentioned that this practice increases word recognition and provided opportunities to apply newly acquired vocabulary in authentic digital environments. This study suggested that vocabulary learning through Spotify could facilitate self-regulated learning activity that promote the students’ lexical development.